Water-based dispersion of resin particles

An aqueous dispersion of resin particles with a covalently bonded composite resin addresses emulsifying and stability issues, resulting in stable toner production with improved image quality.

JP7606338B2Active Publication Date: 2024-12-25KAO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020207030
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-14
Publication Date
2024-12-25
Estimated Expiration
2040-12-14

AI Technical Summary

Technical Problem

Existing aqueous dispersions of binder resin particles for toners in electrophotography face challenges in emulsifying properties and stability, particularly when composite resins with different resin components are used, leading to inconsistent particle size and stability issues.

Method used

The development of an aqueous dispersion of resin particles comprising a composite resin linked by covalent bonds between a polyester resin and an addition polymerization resin, with controlled insoluble components in methyl ethyl ketone between 4% to 35% by mass, allowing for stable emulsification and phase inversion to achieve suitable particle size and reduced viscosity.

Benefits of technology

The resulting resin particles exhibit excellent emulsifying properties and stability, enabling the production of high-quality toners with narrow particle size distribution and improved image quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606338000001
    Figure 0007606338000001
  • Figure 0007606338000002
    Figure 0007606338000002
  • Figure 0007606338000003
    Figure 0007606338000003
Patent Text Reader

Abstract

To provide an aqueous dispersion of resin particles having excellent emulsifiability and stability.SOLUTION: The present invention pertains to an aqueous dispersion of resin particles in which the resin constituting the resin particles includes a composite resin with a polyester resin-derived constitutional unit and an addition polymer resin-derived constitutional unit being covalently linked to each other. The composite resin has the amount of insoluble component in methyl ethyl ketone of 4 mass% or more and 35 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous dispersion of resin particles and a method for producing the same, and more particularly to an aqueous dispersion of binder resin particles for toner and a method for producing the same. [Background technology]

[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of electrophotographic toners that can meet the demands of higher image quality and higher speeds. In order to meet the demands of higher image quality, a method for obtaining a toner with a narrow particle size distribution and small particle size is being carried out, in which fine resin particles or the like are aggregated and fused in an aqueous medium to obtain a toner, namely, a chemical toner, which is produced by an aggregation and fusion method (emulsion aggregation method, aggregation and coalescence method).

[0003] For example, Patent Document 1 discloses a dispersion (D) in which a dispersoid (A) is dispersed in a solvent (B), with the objective of providing a dispersion in which various fine particles such as solid particles are finely dispersed in a dispersion solvent and the dispersion contains few coarse particles, a method for producing the dispersion, and a method for producing resin particles and toner using the dispersion, wherein the dispersoid (A) satisfies [Condition 1] a melting point of 30°C to 100°C, [Condition 2] a median diameter of 0.05 μm to 3.0 μm, [Condition 3] the amount of coarse particles is 1.0 vol% or less, and [Condition 4] a non-spherical shape with a primary particle diameter of 10 nm to 600 nm when converted into a sphere. Patent Document 2 discloses a method for producing a toner for developing electrostatic images, the method comprising the steps of: mixing a crystalline resin (B) and an amorphous composite resin (A) in the presence of a basic compound to obtain a resin mixture; adding an aqueous medium to the obtained resin mixture to perform phase inversion emulsification to obtain an aqueous dispersion of resin particles (I); aggregating the resin particles in the aqueous dispersion of resin particles (I) to obtain an aqueous dispersion of aggregated particles; and fusing the aggregated particles in the aqueous dispersion of aggregated particles to obtain an aqueous dispersion of fused particles, for the purpose of providing a method for producing a toner for developing electrostatic images, the method comprising the steps of: mixing a crystalline resin (B) and an amorphous composite resin (A) in the presence of a basic compound to obtain a resin mixture; [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-091575 A [Patent Document 2] JP 2018-018069 A Summary of the Invention [Problem to be solved by the invention]

[0005] Further improvements are required in terms of emulsifiability and stability for aqueous dispersions (emulsions) of binder resin particles for toners used in the production of chemical toners. From the viewpoint of excellent emulsifiability and stability, it is important to stably obtain fine resin particles, but when the resin is a composite resin in which resin components with different properties are bonded together, the various properties of the resin affect the stability of the particles in the aqueous medium, so it is necessary to find appropriate conditions for each resin. The present invention relates to an aqueous dispersion of resin particles having excellent emulsifiability and stability. [Means for solving the problem]

[0006] The present invention relates to the following [1] and [2]. [1] An aqueous dispersion of resin particles, wherein the resin constituting the resin particles contains a composite resin in which a constituent part derived from a polyester resin and a constituent part derived from an addition polymerization resin are covalently linked, and the amount of insoluble components in the composite resin in methyl ethyl ketone is 4% by mass or more and 35% by mass or less. [2] A method for producing an aqueous dispersion of resin particles according to [1], comprising the steps of dissolving the composite resin in an organic solvent, and then adding an aqueous medium to the organic solvent solution of the composite resin to effect phase inversion emulsification. Effect of the Invention

[0007] The aqueous dispersion of the resin particles of the present invention is excellent in emulsifiability and stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The definitions of various terms used in this specification are given below. Whether a resin is crystalline or amorphous is determined by the crystallinity index. The crystallinity index is defined as the ratio of the softening point of the resin to the maximum endothermic peak temperature (softening point (°C) / maximum endothermic peak temperature (°C)) in the measurement method described in the examples below. A crystalline resin is a resin with a crystallinity index of 0.6 or more and 1.4 or less. A non-crystalline resin is one in which no endothermic peak is observed, or, if an endothermic peak is observed, the crystallinity index is less than 0.6 or more than 1.4. The crystallinity index can be appropriately adjusted by the types and ratios of raw material monomers, as well as production conditions such as reaction temperature, reaction time, and cooling rate.

[0009] The carboxylic acid component of the polyester resin includes not only the compound itself, but also anhydrides that decompose during the reaction to generate an acid, and alkyl esters of each carboxylic acid (alkyl groups having 1 to 3 carbon atoms). With respect to hydrocarbon groups, the references "(iso or tertiary)" and "(iso)" in parentheses refer to both the cases with and without the prefixes present; the absence of the prefixes indicates normal. "(Meth)acrylic acid" means at least one selected from acrylic acid and methacrylic acid. "(Meth)acrylate" means at least one selected from acrylate and methacrylate. The "(meth)acryloyl group" means at least one selected from an acryloyl group and a methacryloyl group. "Main chain" means the relatively longest connecting chain in an addition polymer.

[0010] Volume Median Particle Size (D 50 )" is the particle size at which the cumulative volume frequency calculated by volume fraction is 50% starting from the smallest particle size. The coefficient of variation of particle size distribution (hereinafter, simply referred to as "CV value") is a value expressed by the following formula: The volume average particle size in the following formula is the particle size obtained by multiplying the particle size of all measured particles by the volume of the particle, and dividing the sum by the total volume of the measured particles. CV value (%) = [Standard deviation of particle size distribution (μm) / Volume average particle size (μm)] x 100

[0011] [Water-based dispersion of resin particles] The aqueous dispersion of resin particles of the present invention (hereinafter also referred to as "resin particle dispersion") contains a composite resin in which a polyester resin-derived component and an addition polymerization resin-derived component are covalently bonded to each other, and the composite resin has an insoluble content in methyl ethyl ketone of 4% by mass to 35% by mass. This provides an aqueous dispersion of resin particles with excellent emulsifiability and stability.

[0012] The reason why the aqueous dispersion of resin particles of the present invention has excellent emulsifiability and stability is not clear, but is thought to be as follows. In the present invention, when obtaining an aqueous dispersion of a composite resin in which a constituent part derived from a polyester resin and a constituent part derived from an addition polymerization resin are covalently bonded, the composite resin is used in which the amount of insoluble components in methyl ethyl ketone of the composite resin is controlled to be in the range of 4% by mass or more and 35% by mass or less, thereby making it possible to stably obtain resin particles having a particle size suitable for the emulsion aggregation method. When the amount of insoluble components in methyl ethyl ketone of the composite resin is 35% by mass or less, the insoluble components can be prevented from aggregating while holding the solvent during the production of the resin particle dispersion, so that the particle size of the resin particles can be prevented from becoming large and becoming coarse particles after phase inversion emulsification in water. On the other hand, when the amount of insoluble components in methyl ethyl ketone of the composite resin is 4% by mass or more, the particle size of the resin particles becomes small and the surface area becomes large during the production of the resin particle dispersion, and the viscosity increase of the resin particle dispersion during standing caused by the strong interaction between the particles is suppressed. As a result, it is presumed that an aqueous dispersion of resin particles having an appropriate particle size and excellent emulsification and stability is obtained. The above-mentioned mechanism regarding the effect of the present invention is merely a presumption, and the present invention is not limited thereto.

[0013] 1. Resin particles In the present invention, the resin constituting the resin particles includes a composite resin in which a constituent part derived from a polyester resin and a constituent part derived from an addition polymerization resin are linked by a covalent bond.

[0014] 1-1.Composite resin In the composite resin, a constituent part derived from a polyester resin (hereinafter also referred to as a "polyester resin segment") and a constituent part derived from an addition polymerization resin (hereinafter also referred to as an "addition polymerization resin segment") are linked by a covalent bond. The composite resin preferably contains a constitutional unit derived from a bireactive monomer that is bonded to the polyester resin segment and the addition polymerization resin segment via a covalent bond. In addition, the composite resin is preferably amorphous.

[0015] 1-1-1. Polyester resin-derived components (polyester resin segments) The polyester resin segment is a polycondensation product of an alcohol component and a carboxylic acid component.

[0016] Examples of the alcohol component include aromatic diols, alkylene oxide adducts of aromatic diols, linear or branched aliphatic diols, alicyclic diols, and trihydric or higher polyhydric alcohols. These alcohol components may be used alone or in combination. Among these, alkylene oxide adducts of aromatic diols are preferred.

[0017] The alkylene oxide adduct of an aromatic diol is preferably an alkylene oxide adduct of bisphenol A, more preferably an alkylene oxide adduct of formula (I): [ka] (In the formula, OR 1 and R 2 O is an oxyalkylene group, and R 1 and R 2 are each independently an ethylene group or a propylene group, x and y each represent the average number of moles of alkylene oxide added, each being a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 4 or less. It is an alkylene oxide adduct of bisphenol A represented by the formula:

[0018] Examples of the alkylene oxide adduct of bisphenol A include a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A. These may be used alone or in combination. Among these, the propylene oxide adduct of bisphenol A is preferred.

[0019] The content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, preferably 100 mol %.

[0020] Examples of linear or branched aliphatic diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol. Examples of alicyclic diols include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and adducts of hydrogenated bisphenol A with alkylene oxides having 2 to 4 carbon atoms (average number of moles added: 2 to 12). Examples of trihydric or higher polyhydric alcohols include glycerin, pentaerythritol, trimethylolpropane, and sorbitol. These alcohol components may be used alone or in combination of two or more.

[0021] Examples of the carboxylic acid component include dicarboxylic acids and polycarboxylic acids having 3 or more carboxylic acids. These carboxylic acid components may be used alone or in combination of two or more.

[0022] Examples of dicarboxylic acids include aromatic dicarboxylic acids, linear or branched aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, at least one selected from the group consisting of aromatic dicarboxylic acids and linear or branched aliphatic dicarboxylic acids is preferred. Examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. The amount of aromatic dicarboxylic acid in the carboxylic acid component is preferably 20 mol% or more, more preferably 30 mol% or more, even more preferably 40 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less, even more preferably 75 mol% or less.

[0023] The linear or branched aliphatic dicarboxylic acid preferably has 2 or more, more preferably 3 or more, and preferably has 30 or less, more preferably 20 or less. Examples of linear or branched aliphatic dicarboxylic acids include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, azelaic acid, and succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms. Examples of succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, fumaric acid and sebacic acid are preferred. The amount of the linear or branched aliphatic dicarboxylic acid in the carboxylic acid component is preferably 1 mol % or more, more preferably 10 mol % or more, and is preferably 50 mol % or less, more preferably 30 mol % or less.

[0024] The trivalent or higher polyvalent carboxylic acid is preferably a trivalent carboxylic acid, such as trimellitic acid. When a trivalent or higher polycarboxylic acid is contained, the amount of the trivalent or higher polycarboxylic acid in the carboxylic acid component is preferably 3 mol % or more, more preferably 5 mol % or more, even more preferably 8 mol % or more, and is preferably 30 mol % or less, more preferably 20 mol % or less. These carboxylic acid components may be used alone or in combination of two or more.

[0025] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0026] 1-1-2. Components derived from addition polymerization resin (addition polymerization resin segment) The addition polymerization resin segment is preferably an addition polymer of raw material monomers containing a styrene-based compound.

[0027] The styrene-based compound may be unsubstituted or substituted styrene. Examples of the substituent on styrene include an alkyl group having 1 to 5 carbon atoms, a halogen atom, an alkoxy group having 1 to 5 carbon atoms, a sulfo group, or a salt thereof. Examples of styrene-based compounds include styrene, methylstyrene, α-methylstyrene, β-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, methoxystyrene, styrenesulfonic acid, and salts thereof. Among these, styrene is preferred. In the raw material monomers of the addition polymerization resin segment, the content of the styrene-based compound is preferably 50% by mass or more, more preferably 65% ​​by mass or more, even more preferably 70% by mass or more, and is 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less.

[0028] Examples of raw material monomers other than styrene-based compounds include (meth)acrylic acid esters such as alkyl (meth)acrylate, benzyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; olefins such as ethylene, propylene, and butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as vinyl methyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone. Among these, (meth)acrylic acid esters are preferred, and alkyl (meth)acrylates are more preferred.

[0029] From the viewpoint of obtaining a better image density, the number of carbon atoms in the alkyl group in the alkyl (meth)acrylate is preferably 1 or more, more preferably 4 or more, even more preferably 10 or more, still more preferably 14 or more, and is preferably 24 or less, more preferably 22 or less, even more preferably 20 or less.

[0030] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, (iso or tertiary)butyl (meth)acrylate, (iso)amyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, (iso)dodecyl (meth)acrylate, (iso)palmityl (meth)acrylate, (iso)stearyl (meth)acrylate, and (iso)behenyl (meth)acrylate. Among these, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate are preferred, dodecyl (meth)acrylate and stearyl (meth)acrylate are more preferred, and stearyl methacrylate is even more preferred.

[0031] In the raw material monomers of the addition polymerization resin segment, the content of the (meth)acrylic acid ester is preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 15 mass% or more, and preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 30 mass% or less.

[0032] The total amount of the styrene-based compound and the (meth)acrylic acid ester in the raw material monomers of the addition polymerization resin segment is preferably 80 mass % or more, more preferably 90 mass % or more, even more preferably 95 mass % or more, and still more preferably 100 mass %.

[0033] 1-1-3. Building blocks derived from bireactive monomers The composite resin preferably has a bireactive monomer-derived structural unit covalently bonded to the polyester resin segment and the addition polymerization resin segment. The "bireactive monomer-derived structural unit" refers to a unit formed by reaction of the functional group and the unsaturated bond site of the bireactive monomer.

[0034] Examples of the bireactive monomer include addition polymerizable monomers having at least one functional group selected from hydroxyl group, carboxyl group, epoxy group, primary amino group, and secondary amino group in the molecule. Among these, from the viewpoint of reactivity, addition polymerizable monomers having at least one functional group selected from hydroxyl group and carboxyl group are preferred, and addition polymerizable monomers having a carboxyl group are more preferred. Examples of the addition polymerizable monomers having a carboxyl group include acrylic acid, methacrylic acid, fumaric acid, and maleic acid. Among these, from the viewpoint of reactivity in both polycondensation reaction and addition polymerization reaction, acrylic acid and methacrylic acid are preferred, and acrylic acid is more preferred.

[0035] The amount of the constitutional units derived from the bireactive monomer is preferably 1 part by mol or more, more preferably 5 parts by mol or more, and even more preferably 8 parts by mol or more, relative to 100 parts by mol of the alcohol component of the polyester resin segment of the composite resin, and is preferably 30 parts by mol or less, more preferably 25 parts by mol or less, and even more preferably 20 parts by mol or less.

[0036] 1-1-4. Building blocks derived from hydrocarbon wax The composite resin may further contain a structural unit derived from a hydrocarbon wax having at least one of a carboxy group and a hydroxyl group.

[0037] The hydrocarbon wax-derived component is, for example, a hydrocarbon wax whose hydroxyl or carboxyl group has reacted and covalently bonded to a polyester resin segment. The hydrocarbon wax preferably has at least one of a carboxy group and a hydroxyl group. The hydrocarbon wax may have either a hydroxyl group or a carboxy group, or both, but preferably has a hydroxyl group and a carboxy group. The hydrocarbon wax can be obtained, for example, by modifying an unmodified hydrocarbon wax by a known method. Examples of raw materials for the hydrocarbon wax include paraffin wax, Fischer-Tropsch wax, microcrystalline wax, polyethylene wax, and polypropylene wax. Among these, paraffin wax and Fischer-Tropsch wax are preferred.

[0038] Commercially available examples of hydrocarbon waxes having hydroxyl groups include "Unilin 700," "Unilin 425," and "Unilin 550" (all manufactured by Baker Petrolite).

[0039] Examples of the hydrocarbon wax having a carboxy group include acid-modified hydrocarbon waxes. An example of a commercially available product of a hydrocarbon wax having a carboxy group is maleic anhydride modified ethylene-propylene copolymer "HIWAX 1105A" (manufactured by Mitsui Chemicals, Inc.).

[0040] Commercially available examples of hydrocarbon waxes having a hydroxyl group and a carboxyl group include "PARACOL 6420", "PARACOL 6470", and "PARACOL 6490" (all manufactured by Nippon Seiro Co., Ltd.).

[0041] The hydroxyl value of the hydrocarbon wax is preferably 35 mgKOH / g or more, more preferably 50 mgKOH / g or more, even more preferably 70 mgKOH / g or more, and is preferably 180 mgKOH / g or less, more preferably 150 mgKOH / g or less, even more preferably 120 mgKOH / g or less.

[0042] The acid value of the hydrocarbon wax is preferably 1 mgKOH / g or more, more preferably 5 mgKOH / g or more, even more preferably 10 mgKOH / g or more, and preferably 30 mgKOH / g or less, more preferably 25 mgKOH / g or less, even more preferably 20 mgKOH / g or less.

[0043] The sum of the hydroxyl value and the acid value of the hydrocarbon wax is preferably 35 mgKOH / g or more, more preferably 40 mgKOH / g or more, even more preferably 60 mgKOH / g or more, and is preferably 210 mgKOH / g or less, more preferably 175 mgKOH / g or less, even more preferably 140 mgKOH / g or less.

[0044] The number average molecular weight of the hydrocarbon wax is preferably 500 or more, more preferably 600 or more, even more preferably 700 or more, and preferably 2000 or less, more preferably 1700 or less, even more preferably 1500 or less. The hydroxyl value and acid value of the hydrocarbon wax are measured by the method described in the Examples. The number average molecular weight of the hydrocarbon wax is measured by gel permeation chromatography using chloroform as a solvent and polystyrene as a standard substance.

[0045] The content of the polyester resin segment in the composite resin is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 55% by mass or more, relative to the total amount of the polyester resin segment, the addition polymerization resin segment, and the constitutional units derived from the bireactive monomer, and is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 75% by mass or less.

[0046] The content of the addition polymerization resin segment in the composite resin is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 25% by mass or more, relative to the total amount of the polyester resin segment, the addition polymerization resin segment, and the constitutional units derived from the bireactive monomer, and is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 45% by mass or less.

[0047] The amount of the constitutional units derived from the bireactive monomer in the composite resin is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 0.8 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, based on the total amount of the polyester resin segment, the addition polymerization resin segment, and the constitutional units derived from the bireactive monomer.

[0048] The amount of the constituent units derived from the hydrocarbon wax in the composite resin is, relative to 100 parts by mass of the total amount of the polyester resin segment, the addition polymerization resin segment, and the constituent units derived from the bireactive monomer, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less.

[0049] In the composite resin, the total amount of the polyester resin segment, the addition polymerization resin segment, the constitutional units derived from the bireactive monomer, and the constitutional units derived from the hydrocarbon wax is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more, and is 100 mass% or less, preferably 100 mass%.

[0050] The above amount is calculated based on the ratio of the amounts of the polyester resin segment, raw material monomer for the addition polymerization resin segment, bireactive monomer, structural unit derived from hydrocarbon wax, and radical polymerization initiator, and does not include the amount of dehydration due to polycondensation in the polyester resin segment, etc. When a radical polymerization initiator is used, the mass of the radical polymerization initiator is calculated by including it in the addition polymerization resin segment.

[0051] [Method for producing composite resin] The composite resin may be produced, for example, by a method including a step A of carrying out a polycondensation reaction between an alcohol component and a carboxylic acid component, and a step B of carrying out an addition polymerization reaction between a raw material monomer for the addition polymerization resin segment and a bireactive monomer. When the composite resin has a structural unit derived from a hydrocarbon wax, in the above-mentioned step A, for example, a polycondensation reaction of an alcohol component and a carboxylic acid component is carried out in the presence of a hydrocarbon wax having at least one of a hydroxyl group and a carboxyl group. Step B may be carried out after step A, step B may be carried out after step A, or step A and step B may be carried out simultaneously.

[0052] (Process A) In step A, if necessary, polycondensation may be performed using an esterification catalyst such as tin(II) di(2-ethylhexanoate), dibutyltin oxide, titanium diisopropylate bistriethanolamine, etc., in an amount of 0.01 part by mass or more and 5 parts by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component; or an esterification promoter such as gallic acid (same as 3,4,5-trihydroxybenzoic acid), etc., in an amount of 0.001 part by mass or more and 0.5 part by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. In addition, when a monomer having an unsaturated bond such as fumaric acid is used in the polycondensation reaction, a radical polymerization inhibitor may be used, if necessary, in an amount of preferably 0.001 to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. An example of the radical polymerization inhibitor is 4-tert-butylcatechol.

[0053] The temperature of the polycondensation reaction is preferably 120° C. or higher, more preferably 160° C. or higher, and even more preferably 180° C. or higher, and is preferably 250° C. or lower, more preferably 245° C. or lower, and even more preferably 240° C. or lower. The polycondensation may be carried out in an inert gas atmosphere.

[0054] (Process B) Examples of the polymerization initiator for the addition polymerization reaction include peroxides such as dibutyl peroxide, persulfates such as sodium persulfate, and azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile). The amount of the radical polymerization initiator used is preferably 1 part by mass or more and 20 parts by mass or less based on 100 parts by mass of the raw material monomer of the addition polymerization resin segment. The temperature of the addition polymerization reaction is preferably 110° C. or higher, more preferably 130° C. or higher, and preferably 220° C. or lower, more preferably 200° C. or lower, and further preferably 180° C. or lower.

[0055] A preferred method is to subject a part of the carboxylic acid component to a polycondensation reaction in step A, then carry out step B, and then add the remainder of the carboxylic acid component to the polymerization system to further proceed with the polycondensation reaction in step A and the reaction with the bireactive monomer as necessary. Of the carboxylic acid components that are raw materials for the polyester resin segment, it is preferred that a trivalent or higher polyvalent carboxylic acid (e.g., trimellitic acid) is not added in the initial polycondensation reaction in step A, but is added after carrying out step B. When the reaction rate of the polycondensation reaction in the first step A reaches, for example, 90% or more, the pressure in the system is reduced and cooled, and then the raw material monomers of the addition polymerization resin segment and the bireactive monomer are dropped into the system to carry out the addition polymerization reaction in step B. The dropping temperature of the raw material monomers and bireactive monomers for the addition polymerization resin segment in step B is preferably 155° C. or more, more preferably 157° C. or more, even more preferably 160° C. or more, and preferably 190° C. or less, more preferably 180° C. or less, and even more preferably 170° C. or less. The dropping time of the raw material monomers and bireactive monomers for the addition polymerization resin segment in step B is preferably 0.5 hours or more, more preferably 1.5 hours or more, even more preferably 2.5 hours or more, and preferably 5 hours or less, more preferably 4 hours or less, and even more preferably 3.5 hours or less. After carrying out step B, the remainder of the carboxylic acid component, which is the raw material of the polyester resin segment, is added to the polymerization system, and the polycondensation reaction of step A and the reaction with the bireactive monomer as necessary are further promoted. The reaction time of the trivalent or higher polyvalent carboxylic acid (e.g., trimellitic acid) is preferably 4 hours or more, more preferably 5 hours or more, even more preferably 6 hours or more, and preferably 8 hours or less, more preferably 7.5 hours or less, even more preferably 7 hours or less.

[0056] [Physical properties of composite resin] The softening point of the composite resin is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher, and is preferably 140°C or lower, more preferably 125°C or lower, and even more preferably 130°C or lower.

[0057] The glass transition temperature of the composite resin is preferably 30°C or higher, more preferably 40°C or higher, even more preferably 45°C or higher, and preferably 80°C or lower, more preferably 70°C or lower, even more preferably 60°C or lower.

[0058] The acid value of the composite resin is preferably 10 mgKOH / g or more, more preferably 15 mgKOH / g or more, even more preferably 18 mgKOH / g or more, and preferably 40 mgKOH / g or less, more preferably 35 mgKOH / g or less, even more preferably 30 mgKOH / g or less.

[0059] The softening point, glass transition temperature and acid value of the composite resin can be appropriately adjusted by the type and amount of raw material monomer, and production conditions such as reaction temperature, reaction time, cooling rate, etc., and these values ​​are determined by the method described in the Examples. When two or more composite resins are used in combination, it is preferable that the softening point, glass transition temperature and acid value of the mixture thereof are each within the above-mentioned ranges.

[0060] In the present invention, the amount of insoluble components of the composite resin in methyl ethyl ketone is 4% by mass or more and 35% by mass or less. When the amount of insoluble components of the composite resin in methyl ethyl ketone is 35% by mass or less, the insoluble components can be prevented from aggregating while holding the solvent during the production of the resin particle dispersion, and therefore the resin particles can be prevented from becoming large in particle size and becoming coarse particles after phase inversion emulsification in water. On the other hand, when the amount of insoluble components of the composite resin in methyl ethyl ketone is 4% by mass or more, the resin particles can be prevented from becoming small in particle size and having a large surface area during the production of the resin particle dispersion, and the viscosity increase of the resin particle dispersion during standing, which occurs due to the strong interaction between the particles, can be prevented. The amount of insoluble components of the composite resin in methyl ethyl ketone is preferably 5% by mass or more, and is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. Although methyl ethyl ketone is a typical solvent used during the production of the resin particle dispersion, the organic solvent used for phase inversion emulsification is not limited to methyl ethyl ketone, as described later. The amount of insoluble components of the composite resin in the organic solvent used for phase inversion emulsification varies depending on the type of organic solvent. In the present invention, however, the physical properties of the composite resin are specified by specifying the amount of insoluble components of the composite resin in methyl ethyl ketone as an indicator of the amount of insoluble components of the composite resin in the organic solvent used for phase inversion emulsification.

[0061] In the present invention, the "amount of the component insoluble in methyl ethyl ketone of the composite resin" specifically means the mass of the resin component that is not dissolved in methyl ethyl ketone in the following measurement. (Method for measuring the amount of insoluble matter in composite resin in methyl ethyl ketone) 2.5 g of resin sample and 12.0 g of methyl ethyl ketone are placed in a 20 mL sample vial and stirred at 73°C for 1 hour. Then, using a tabletop centrifuge, the mixture is centrifuged at 20°C and 25,000 rpm for 5 hours, and the supernatant is removed. The insoluble components that have precipitated in the centrifuge tube are dried under reduced pressure at 80°C overnight, and the mass (g) of the insoluble components is measured. The amount of insoluble components is calculated according to the following formula: Amount of insoluble matter (mass%) = [Mass of insoluble matter (g) / 2.5] x 100

[0062] The content of the composite resin in the resin particles is preferably 40% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, still more preferably 65% ​​by mass or more, and is 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, still more preferably 85% by mass or less, and still more preferably 75% by mass or less.

[0063] 1-2.Crystalline polyester resin The resin constituting the resin particles may further contain a resin other than the composite resin. It is preferable that the resin constituting the resin particles further contains a crystalline polyester. The crystalline polyester resin is a polycondensation product of an alcohol component and a carboxylic acid component.

[0064] The alcohol component is preferably an α,ω-aliphatic diol. The carbon number of the α,ω-aliphatic diol is preferably 2 or more, more preferably 4 or more, and even more preferably 6 or more, and is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred, and 1,10-decanediol is more preferred.

[0065] The amount of the α,ω-aliphatic diol in the alcohol component is preferably 80 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, preferably 100 mol %.

[0066] The alcohol component may contain other alcohol components different from the α,ω-aliphatic diol. Examples of the other alcohol components include aliphatic diols other than α,ω-aliphatic diols, such as 1,2-propanediol and neopentyl glycol; aromatic diols, such as alkylene oxide adducts of bisphenol A; and trihydric or higher alcohols, such as glycerin, pentaerythritol, and trimethylolpropane. These alcohol components may be used alone or in combination.

[0067] The carboxylic acid component is preferably an aliphatic dicarboxylic acid, more preferably a straight-chain aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid has preferably 4 or more, more preferably 8 or more, and even more preferably 10 or more carbon atoms, and preferably 14 or less, and more preferably 12 or less. Examples of the aliphatic dicarboxylic acid include fumaric acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among these, sebacic acid and tetradecanedioic acid are preferred, and sebacic acid is more preferred. These carboxylic acid components may be used alone or in combination.

[0068] The amount of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol % or more, more preferably 90 mol % or more, further preferably 95 mol % or more, and is 100 mol % or less, preferably 100 mol %.

[0069] The carboxylic acid component may contain other carboxylic acid components different from the aliphatic dicarboxylic acid. Examples of other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid, and polyvalent carboxylic acids having three or more carboxylic acids. These carboxylic acid components may be used alone or in combination.

[0070] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0071] The crystalline polyester resin can be produced, for example, by the same method as in step A in the production of the composite resin described above.

[0072] [Physical Properties of Crystalline Polyester Resin] The softening point of the crystalline polyester resin is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher, and is preferably 150°C or lower, more preferably 120°C or lower, and even more preferably 100°C or lower.

[0073] The melting point of the crystalline polyester resin is preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 70° C. or higher, and is preferably 100° C. or lower, more preferably 90° C. or lower, and even more preferably 85° C. or lower.

[0074] The acid value of the crystalline polyester resin is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, even more preferably 15 mgKOH / g or more, and is preferably 35 mgKOH / g or less, more preferably 25 mgKOH / g or less, even more preferably 20 mgKOH / g or less.

[0075] The softening point, melting point and acid value of the crystalline polyester resin can be appropriately adjusted by the type and amount of raw material monomer, and production conditions such as reaction temperature, reaction time, cooling rate, etc., and are determined by the method described in the Examples below. When two or more crystalline polyester resins are used in combination, it is preferable that the softening point, melting point and acid value obtained as a mixture thereof are each within the above-mentioned ranges.

[0076] When the resin particles contain a crystalline polyester resin, the content of the crystalline polyester resin in the resin particles is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, still more preferably 25% by mass or more, and preferably 60% by mass or less, more preferably 50% by mass or less, still more preferably 40% by mass or less, and still more preferably 35% by mass or less.

[0077] When the resin particles contain a crystalline polyester resin, the mass ratio of the composite resin to the crystalline polyester resin [composite resin / crystalline resin] is preferably 40 / 60 or more, more preferably 50 / 50 or more, even more preferably 60 / 40 or more, still more preferably 65 / 35 or more, and preferably 95 / 5 or less, more preferably 90 / 10 or less, still more preferably 85 / 15 or less, and still more preferably 75 / 25 or less.

[0078] 2. Method for producing aqueous dispersion of resin particles The aqueous dispersion of resin particles can be produced by applying a known method, but it is preferable to disperse the resin particles by a phase inversion emulsification method. That is, the method for producing the aqueous dispersion of resin particles of the present invention preferably includes a step of dissolving the composite resin in an organic solvent, and then adding an aqueous medium to the organic solvent solution of the composite resin to perform phase inversion emulsification.

[0079] The organic solvent used for phase inversion emulsification is not particularly limited as long as it dissolves the resin, but from the viewpoint of facilitating phase inversion, examples include alcohol-based solvents such as ethanol, isopropanol, isobutanol, etc.; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ketone, etc.; ether-based solvents such as dibutyl ether, tetrahydrofuran, dioxane, etc.; and acetate-based solvents such as ethyl acetate, isopropyl acetate, etc. Among these, from the viewpoint of easy removal from the mixed solution after addition of the aqueous medium, ketone-based solvents and acetate-based solvents are preferred, methyl ethyl ketone, ethyl acetate, isopropyl acetate are more preferred, and methyl ethyl ketone is even more preferred.

[0080] It is preferable to add a neutralizing agent to the organic solvent solution. Examples of the neutralizing agent include basic substances. Examples of the basic substance include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, and nitrogen-containing basic substances such as ammonia, trimethylamine, and diethanolamine. The degree of neutralization of the resin contained in the resin particles is preferably 10 mol % or more, more preferably 20 mol % or more, even more preferably 40 mol % or more, and preferably 100 mol % or less, more preferably 80 mol % or less, even more preferably 70 mol % or less. The degree of neutralization of the resin contained in the resin particles can be calculated by the following formula. Degree of neutralization (mol%)=[{weight of neutralizing agent added (g) / equivalent weight of neutralizing agent} / [{weighted average acid value of resin constituting resin particle X (mgKOH / g)×weight of resin constituting resin particle X (g)} / (56×1000)]]×100

[0081] The aqueous medium is preferably one containing water as a main component, and from the viewpoint of improving the dispersion stability of the aqueous dispersion of the resin particles and from the viewpoint of environmental friendliness, the content of water in the aqueous medium is preferably 80% by mass or more, more preferably 90% by mass or more, still more preferably 95% by mass or more, and is 100% by mass or less, preferably 100% by mass. As the water, deionized water or distilled water is preferable. Examples of components other than water that may be contained in the aqueous medium include water-soluble organic solvents such as alkyl alcohols having 1 to 5 carbon atoms, dialkyl ketones having a total of 3 to 5 carbon atoms, such as acetone and methyl ethyl ketone, and cyclic ethers, such as tetrahydrofuran. Among these, methyl ethyl ketone is preferred.

[0082] The organic solvent solution is stirred while the aqueous medium is gradually added to cause phase inversion. From the viewpoint of improving the dispersion stability of the resin particles, the temperature of the organic solvent solution when the aqueous medium is added is preferably not less than the glass transition temperature of the resin constituting the resin particles, more preferably not less than 50°C, even more preferably not less than 60°C, and is preferably not more than 100°C, more preferably not more than 90°C, even more preferably not more than 80°C.

[0083] After the phase inversion emulsification, if necessary, the organic solvent may be removed from the obtained dispersion by distillation, etc. In this case, the amount of the remaining organic solvent in the dispersion is preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably substantially 0% by mass.

[0084] Volume median diameter D of resin particles in aqueous dispersion 50 From the viewpoint of obtaining a toner capable of obtaining high quality images, the particle diameter is preferably 80 nm or more, more preferably 100 nm or more, and is preferably 500 nm or less, more preferably 250 nm or less, and further preferably 220 nm or less. From the viewpoint of obtaining a toner that can obtain high-quality images, the CV value of the resin particles in the aqueous dispersion is preferably 10% or more, more preferably 20% or more, and is preferably 60% or less, more preferably 40% or less. Volume median particle size D 50 The CV value is determined by the method described in the Examples.

[0085] 3. Toner manufacturing method The aqueous dispersion of resin particles of the present invention is excellent in emulsifiability and stability, and therefore can be preferably applied to the production of toner, and more preferably applied to the production of chemical toner. The method for producing the toner is not particularly limited, and a known method can be applied. For example, the toner production methods described in JP-A-2019-139229 and JP-A-2019-152855 can be cited by reference.

[0086] For example, the toner manufacturing method includes the following steps: A step of aggregating resin particles and colorant particles using the aqueous dispersion of resin particles of the present invention to obtain aggregated particles (hereinafter also referred to as "step 1"); and A step of fusing the aggregated particles in an aqueous medium (hereinafter also referred to as "step 2") A method comprising the steps of:

[0087] 3-1. Process 1 In step 1, the resin particles and colorant particles are aggregated using the aqueous dispersion of the resin particles of the present invention to obtain aggregated particles. In addition to the resin particles and colorant particles, additives such as wax may be aggregated. Examples of additives include wax, charge control agents, magnetic powder, flowability improvers, conductivity regulators, reinforcing fillers such as fibrous substances, antioxidants, antiaging agents, and cleaning improvers. In step 1, the aqueous dispersion of the resin particles of the present invention, the aqueous dispersion of the colorant particles, and any additives are mixed by a conventional method. From the viewpoint of efficient aggregation, it is preferable to add an aggregating agent to the mixed dispersion obtained by the mixing.

[0088] Examples of the flocculant include cationic surfactants such as quaternary salts, organic flocculants such as polyethyleneimine, and inorganic flocculants. Examples of the inorganic flocculant include inorganic metal salts such as sodium sulfate, sodium nitrate, sodium chloride, calcium chloride, and calcium nitrate; inorganic ammonium salts such as ammonium sulfate, ammonium chloride, and ammonium nitrate; and divalent or higher metal complexes. From the viewpoint of improving the coagulation properties and obtaining uniformly coagulated particles, inorganic coagulants having a valence of 1 to 5 are preferred, inorganic metal salts having a valence of 1 to 2 and inorganic ammonium salts are more preferred, inorganic ammonium salts are even more preferred, and ammonium sulfate is even more preferred.

[0089] For example, 5 to 50 parts by mass of the aggregating agent is added to a mixed dispersion containing resin particles and colorant particles at 0° C. to 40° C., based on 100 parts by mass of the total amount of the resin, and the resin particles and colorant particles are aggregated in an aqueous medium to obtain aggregated particles. Furthermore, from the viewpoint of promoting aggregation, it is preferable to increase the temperature of the dispersion after adding the aggregating agent.

[0090] The aggregation may be stopped when the aggregated particles grow to a suitable particle size as toner particles. Examples of a method for stopping the aggregation include a method of cooling the dispersion, a method of adding an aggregation terminator, and a method of diluting the dispersion. From the viewpoint of reliably preventing unnecessary aggregation, a method of stopping the aggregation by adding an aggregation terminator is preferred.

[0091] The aggregation terminator is preferably a surfactant, more preferably an anionic surfactant. Examples of the anionic surfactant include alkylbenzenesulfonate, alkyl sulfate, alkyl ether sulfate, polyoxyalkylene alkyl ether sulfate, etc. These may be used alone or in combination. The aggregation terminator may be added in the form of an aqueous solution. The amount of the aggregation terminator added is preferably 1 part by mass or more, more preferably 5 parts by mass or more, per 100 parts by mass of the resin in the resin particles, from the viewpoint of reliably preventing unnecessary aggregation, and is preferably 60 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, from the viewpoint of reducing residue in the toner.

[0092] Volume median particle size of agglomerated particles D 50 is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6 μm or less.

[0093] 3-2. Process 2 In step 2, the aggregated particles are fused in an aqueous medium, whereby the particles contained in the aggregated particles are fused together to obtain fused particles. The volume median particle size D of the fused particles obtained by fusion50 is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6 μm or less.

[0094] The circularity of the fused particles obtained by fusion is preferably 0.955 or more, more preferably 0.960 or more, and is preferably 0.990 or less, more preferably 0.985 or less, and further preferably 0.980 or less. The fusion is preferably terminated after the above-mentioned preferred circularity is reached.

[0095] <Post-processing process> A post-treatment step may be performed after step 2, and toner particles are obtained by isolating the fused particles. Since the fused particles obtained in step 2 are present in an aqueous medium, it is preferable to first perform solid-liquid separation. For solid-liquid separation, a suction filtration method or the like is preferably used. It is preferable to wash the solid-liquid separation product. In this case, it is preferable to remove the surfactant added, and therefore it is preferable to wash the product with an aqueous medium at a temperature below the cloud point of the surfactant. It is preferable to wash the product several times. Next, drying is preferably performed. Examples of the drying method include vacuum low-temperature drying, vibration-type fluidized bed drying, spray drying, freeze drying, and flash jet drying.

[0096] [Toner Particles] Volume median particle size of toner particles D 50 From the viewpoint of obtaining a high-quality image with the toner and further improving the cleaning properties of the toner, the particle size is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6 μm or less.

[0097] The CV value of the toner particles is preferably 12% or more, more preferably 14% or more, and even more preferably 16% or more, from the viewpoint of improving the productivity of the toner, and is preferably 30% or less, more preferably 26% or less, and even more preferably 23% or less, from the viewpoint of obtaining high-quality images.

[0098] [toner] The toner includes toner particles. Although the toner particles can be used as they are, it is preferable to use the toner after adding a fluidizing agent or the like as an external additive to the surface of the toner particles. Examples of the external additive include fine particles of inorganic materials such as hydrophobic silica, titanium oxide, alumina, cerium oxide, and carbon black, and fine particles of polymers such as polycarbonate, polymethyl methacrylate, and silicone resin. Among these, hydrophobic silica is preferred. When the toner particles are surface-treated using an external additive, the amount of the external additive added is, relative to 100 parts by mass of the toner particles, preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4.5 parts by mass or less, even more preferably 4 parts by mass or less.

[0099] Toners are used for developing electrostatic images in electrophotographic printing. The toners can be used, for example, as one-component developers or mixed with a carrier to form two-component developers. EXAMPLES

[0100] [measurement] [Acid value and hydroxyl value of resin and wax] The acid value and hydroxyl value of the resin and wax were measured in accordance with JIS K0070: 1992, except that the measurement solvent was a mixed solvent of acetone and toluene (acetone:toluene=1:1 (volume ratio)).

[0101] [Softening point, crystallinity index, melting point and glass transition temperature of resin] (1) Softening point Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point. (2) Crystallinity index Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample was weighed into an aluminum pan and cooled to 0°C at a rate of 10°C / min. The sample was then left to stand for 1 minute, and then heated to 180°C at a rate of 10°C / min to measure the amount of heat. The temperature of the peak with the largest peak area among the observed endothermic peaks was taken as the endothermic maximum peak temperature (1), and the crystallinity index was calculated by (softening point (°C)) / (endothermic maximum peak temperature (1) (°C)). (3) Melting point and glass transition temperature Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, and the amount of heat was measured. Among the endothermic peaks observed, the temperature of the peak with the largest peak area was taken as the maximum endothermic peak temperature (2). In the case of a crystalline resin, this peak temperature was taken as the melting point. In the case of an amorphous resin, when a peak was observed, the temperature of the peak was taken as the glass transition temperature. When no peak was observed but a step was observed, the temperature at the intersection of the tangent showing the maximum slope of the curve at the step and an extension of the baseline on the low temperature side of the step was taken as the glass transition temperature.

[0102] [Melting point of wax] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, the amount of heat was measured, and the maximum endothermic peak temperature was taken as the melting point.

[0103] [Volume median particle size D of resin particles, release agent particles, and colorant particles 50 and CV value] (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba Ltd.) (2) Measurement conditions: Add distilled water to the measurement cell and measure the volume median particle size D at a concentration that brings the absorbance into the appropriate range. 50 and volume average particle size were measured. The CV value (coefficient of variation of particle size distribution) was calculated according to the following formula. The volume average particle size in the following formula is the particle size obtained by multiplying the particle size of all measured particles by the volume of the particle and dividing the sum by the total volume of the measured particles. CV value (%) = [Standard deviation of particle size distribution (μm) / Volume average particle size (μm)] x 100

[0104] [Solid Content Concentration of Resin Particle Dispersion, Release Agent Particle Dispersion, and Colorant Particle Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), the moisture content (mass%) of 5 g of the measurement sample was measured at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 min / fluctuation range 0.05%). The solid content concentration was calculated according to the following formula. Solid content concentration (mass%) = 100-moisture (mass%)

[0105] [Amount of insoluble matter in composite resin in methyl ethyl ketone] 2.5 g of resin sample and 12.0 g of methyl ethyl ketone were placed in a 20 mL sample tube and stirred at 73°C for 1 hour. The mixture was then centrifuged at 20°C and 25,000 rpm for 5 hours using a tabletop centrifuge, and the supernatant was removed. The insoluble components precipitated in the centrifuge tube were dried under reduced pressure at 80°C overnight, and the mass (g) of the insoluble components was measured. The amount of insoluble components was calculated according to the following formula. Amount of insoluble matter (mass%) = [Mass of insoluble matter (g) / 2.5] x 100

[0106] [Stability of Resin Particle Dispersion] The resin particle dispersion and deionized water were added to a 50 mL sample vial so that the solid content concentration of the resin particle dispersion was 15 mass%, and 13 samples of 20 g were prepared. Then, 1.46 to 0.11 g of ammonium sulfate was added to each sample vial so that the ammonium ion relative to the total deionized water was 1.3 to 0.1 M (in 0.1 M increments). Then, each sample vial was stirred at 25 ° C for 1 hour on a tabletop pot mill stand (AS ONE Corporation), and then the sample vial was left to stand for 30 minutes. After standing, the sample vial was turned upside down, and the maximum ammonium ion concentration at which the resin particle dispersion settled without increasing in viscosity was compared. Generally, the resin particle dispersion aggregates with each other due to the interaction between the carboxylate at the resin end and the ammonium ion, and the viscosity increases, so the higher the maximum ammonium ion concentration, the better the stability of the resin particle dispersion.

[0107] [Volume median particle diameter of agglomerated particles D 50 〕 Volume median particle size of agglomerated particles D 50 was measured as follows: Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured again, and the volume median particle size D is calculated from the particle size distribution. 50 asked for.

[0108] [Circularity of fused particles] The circularity of the fused particles was measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of fused particles was prepared by diluting with deionized water to a solids concentration of 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode

[0109] [Volume median particle size of toner particles D 50 and CV value] Volume median particle size of toner particles D 50 was measured as follows: The measurement device, aperture diameter, analysis software, and electrolyte were determined based on the volume median particle diameter D 50 The same one used in the measurement was used. Dispersion: Polyoxyethylene lauryl ether "EMULGEN (registered trademark) 109P" (manufactured by Kao Corporation, HLB (hydrophile-lipophile balance) = 13.6) was dissolved in the electrolyte to obtain a dispersion with a concentration of 5 mass %. Dispersion conditions: 10 mg of a measurement sample of dried toner particles was added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Thereafter, 25 mL of the electrolyte was added, and the mixture was further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size D is calculated from the particle size distribution. 50 and volume average particle size D V asked for. The CV value (%) was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size D V ) x 100

[0110] [Resin manufacturing] [Production of amorphous resin] Production Example A1 (Production of Composite Resin A-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 3388g of propylene oxide (2.2) adduct of bisphenol A, 1044g of terephthalic acid, 385g of hydrocarbon wax "Paracol 6490" (manufactured by Nippon Seiro Co., Ltd.), 25g of tin (II) di(2-ethylhexanoate), and 2.5g of gallic acid were added, and the temperature was raised to 235°C over 2 hours while stirring under a nitrogen atmosphere. After that, it was confirmed that the reaction rate reached 90% or more at 235°C, the pressure in the flask was reduced, and the flask was kept at 8kPa for 1 hour, and then cooled to 160°C. Then, a mixture of 2200g of styrene, 550g of stearyl methacrylate, 112g of acrylic acid, and 330g of dibutyl peroxide was added dropwise over 3 hours. After that, after holding for 30 minutes, the temperature was raised to 200°C, and the pressure inside the flask was further reduced and held at 8 kPa for 1 hour. Then, under normal pressure, it was cooled to 190°C, and 134g of fumaric acid, 98g of sebacic acid, 223g of trimellitic anhydride, and 2.5g of 4-tert-butylcatechol were added, and the temperature was raised to 210°C at 10°C / hr. Then, the reaction was carried out at 4 kPa for the reaction time of trimellitic anhydride shown in Table 1, to obtain composite resin A-1. The physical properties are shown in Table 1.

[0111] Production Examples A2 to A12 (Production of Composite Resins A-2 to A-12) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and raw materials other than fumaric acid, sebacic acid, and trimellitic anhydride from the raw material components (A) of the polyester segment shown in Table 1, a hydrocarbon wax "Paracol 6490" (manufactured by Nippon Seiro Co., Ltd.), an esterification catalyst, and an esterification promoter were added, and the temperature was raised to 235°C over 2 hours while stirring under a nitrogen atmosphere. After that, it was confirmed that the reaction rate reached 90% or more at 235°C, the pressure in the flask was reduced, and after maintaining at 8 kPa for 1 hour, it was cooled to the dripping temperature of the raw material monomer (B) shown in the table. Then, a mixed solution of the raw material monomer (B), bireactive monomer, and radical polymerization initiator of the addition polymerization resin segment shown in Table 1 was dripped according to the dripping time of the raw material monomer (B) shown in the table. After that, after maintaining for 30 minutes, the temperature was raised to 200°C, and the pressure in the flask was further reduced and maintained at 8 kPa for 1 hour. Then, the mixture was cooled to 190°C under normal pressure, and fumaric acid, sebacic acid, trimellitic anhydride and a radical polymerization inhibitor, which are the raw material components (A) of the polyester segment shown in Table 1, were added, and the temperature was raised to 210°C at 10°C / hr. Then, the reaction was carried out at 4 kPa for the reaction time of trimellitic anhydride shown in Table 1, to obtain composite resins A-2 to A-12. The physical properties are shown in Table 2.

[0112] [Table 1]

[0113] [Table 2]

[0114] [Production of crystalline resin] Production Example C1 (Production of Crystalline Polyester Resin C-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, 3416g of 1,10-decanediol and 4084g of sebacic acid were added, and the mixture was heated to 135°C while stirring, held at 135°C for 3 hours, and then heated from 135°C to 200°C over 10 hours. Then, 23g of tin(II) di(2-ethylhexanoate) was added, and the mixture was held at 200°C for another hour, after which the pressure in the flask was reduced and the mixture was held under a reduced pressure of 8.3kPa for 1 hour to obtain crystalline polyester resin C-1. The physical properties are shown in Table 3.

[0115] [Table 3]

[0116] [Production of Resin Particle Dispersion (Aqueous Dispersion of Resin Particles)] Example 1 (Production of Resin Particle Dispersion X-1) 210 g of composite resin A-1, 90 g of crystalline polyester resin C-1, and 360 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, and stirred for 2 hours at 73° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 600 g of deionized water was added over 60 minutes while stirring at 280 r / min (circumferential speed 88 m / min) to cause phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. Thereafter, while continuing to stir at 280 r / min (circumferential speed 88 m / min), the aqueous dispersion was cooled to 30°C, and deionized water was added so that the solid content concentration was 20 mass%, to obtain resin particle dispersion X-1.

[0117] Examples 2 to 9 and Comparative Examples 1 to 3 (Production of Resin Particle Dispersions X-2 to X-12) Resin particle dispersions X-2 to X-12 were obtained in the same manner as in Example 1, except that Composite Resin A-1 in Example 1 was changed to Composite Resins A-2 to A-12, respectively.

[0118] The volume median particle diameter D of the obtained resin particles 50 The measurement results for the CV value and the stability of the resin particle dispersion are shown in Table 4.

[0119] Volume median particle size of resin particles D 50 is passed if it is within the range of 100 nm or more and 210 nm or less, and is failed if it is less than 100 nm or more than 210 nm. The CV value is passed if it is within the range of 20% or more and 35% or less, and is failed if it is less than 20% or more than 35%. As for the stability of the resin particle dispersion, it is passed if the maximum ammonium ion concentration is 0.4 M or more, and is failed if it is less than 0.4 M.

[0120] [Table 4]

[0121] The resin particle dispersion of Comparative Example 1 is inferior in stability, while the resin particle dispersions of Comparative Examples 2 and 3 have large and widely varying particle sizes of the resin particles, and are inferior in emulsifiability. In contrast, the resin particle dispersions of Examples 1 to 9 have resin particles having appropriate particle sizes dispersed with small variations, and are excellent in emulsifiability and stability of the resin particle dispersions.

[0122] Reference example (Toner manufacturing) Production Example B1 (Production of Amorphous Resin B-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 5330g of ethylene oxide (2.2) adduct of bisphenol A, 2178g of terephthalic acid, 220g of dodecenylsuccinic anhydride, 120g of adipic acid, 40g of tin (II) di(2-ethylhexanoate), and 4g of gallic acid were added, and the mixture was heated to 235°C under a nitrogen atmosphere while stirring, and then held at 235°C for 10 hours, after which the pressure in the flask was reduced and held at 8kPa for 1 hour. Then, 315g of trimellitic anhydride was added, and the mixture was further held at 230°C for 3 hours. Then, the pressure in the flask was reduced, and the reaction was carried out at 10kPa to obtain amorphous resin B-1.

[0123] Manufacturing Example D1 (Manufacturing of Resin D-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 4313g of a propylene oxide (2.2) adduct of bisphenol A, 818g of terephthalic acid, 727g of succinic acid, 30g of tin (II) di(2-ethylhexanoate), and 3g of gallic acid were added, and the temperature was raised to 235°C while stirring under a nitrogen atmosphere, and the flask was kept at 235°C for 5 hours, after which the pressure in the flask was reduced and kept at 8kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and the flask was cooled to 160°C, and a mixture of 2756g of styrene, 689g of stearyl methacrylate, 142g of acrylic acid, and 413g of dibutyl peroxide was added dropwise over 1 hour while the temperature was kept at 160°C. Thereafter, the temperature was maintained at 160° C. for 30 minutes, and then the temperature was raised to 200° C., and the pressure inside the flask was further reduced and the reaction was carried out at 8 kPa to obtain Resin D-1.

[0124] Production Example Y1 (Production of Resin Particle Dispersion Y-1) 300 g of amorphous resin B-1 and 360 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resin was dissolved over 2 hours at 40° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 40°C, 600g of deionized water was added over 60 minutes while stirring at 280r / min (circumferential speed 88m / min) to cause phase inversion emulsification. The temperature was raised to 73°C, and methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. Thereafter, the aqueous dispersion was cooled to 30°C while stirring at 280r / min (circumferential speed 88m / min), and deionized water was added so that the solid concentration was 20 mass%, to obtain resin particle dispersion Y-1. The volume median particle diameter D of the obtained resin particles was 50 The concentration was 110 nm and the CV value was 24%.

[0125] Production Example Z1 (Production of Resin Particle Dispersion Z-1) 200 g of Resin D-1 and 200 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resin was dissolved over 2 hours at 73° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization was 60 mol% relative to the acid value of Resin D-1, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 700g of deionized water was added over 50 minutes while stirring at 280r / min (circumferential speed 88m / min) to cause phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion liquid. Thereafter, while continuing to stir at 280r / min (circumferential speed 88m / min), the aqueous dispersion liquid was cooled to 30°C, and deionized water was added so that the solid concentration was 20 mass%, thereby obtaining resin particle dispersion liquid Z-1. The volume median particle diameter D of the obtained resin particles was 50 The concentration was 90 nm and the CV value was 23%.

[0126] Production Example P1 (Production of Resin Particle Dispersion P-1) 200 g of Resin D-1 and 200 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resin was dissolved over 2 hours at 73° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 700g of deionized water was added over 50 minutes while stirring at 280r / min (circumferential speed 88m / min) to cause phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. Thereafter, while continuing to stir at 280r / min (circumferential speed 88m / min), the aqueous dispersion was cooled to 30°C, and deionized water was added so that the solid concentration was 20 mass%, to obtain a resin particle dispersion P-1. The volume median particle diameter D of the obtained resin particles was 50 The thickness was 0.09 μm and the CV value was 23%.

[0127] [Production of release agent particle dispersion] Production Example W1 (Production of Release Agent Particle Dispersion W-1) Into a 1 L beaker were added 120 g of deionized water, 86 g of resin particle dispersion P-1, and 40 g of paraffin wax "HNP-9" (manufactured by Nippon Seiro Co., Ltd., melting point 75°C), and the mixture was melted by maintaining the temperature at 90 to 95°C and stirred to obtain a molten mixture. The obtained molten mixture was dispersed for 20 minutes using an ultrasonic homogenizer "US-600T" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) while maintaining the temperature at 90 to 95°C, and then cooled to room temperature (20°C). Deionized water was added to adjust the solid content to 20% by mass, and a release agent particle dispersion W-1 was obtained. The volume median particle diameter D of the release agent particles in the dispersion was 50 The diameter was 0.47 μm and the CV value was 27%.

[0128] Production Example W2 (Production of Release Agent Particle Dispersion W-2) A release agent particle dispersion W-2 was obtained in the same manner as in Production Example W1, except that the type of release agent used was changed to Fischer-Tropsch wax "FNP-0090" (manufactured by Nippon Seiro Co., Ltd., melting point 90°C). 50 The diameter was 0.45 μm and the CV value was 28%.

[0129] [Production of addition polymers] Production Example E1 (Synthesis of Addition Polymer E-1) 16 parts by mass of methacrylic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 44 parts by mass of styrene (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 15 parts by mass (15 parts by mass as solids) of styrene macromonomer "AS-6S" (manufactured by Toagosei Co., Ltd., number average molecular weight 6,000, solids content 50% by mass), and 25 parts by mass of methoxypolyethylene glycol methacrylate "BLEMMER PME-200" (NOF Corporation) were mixed to prepare 115 parts by mass of a monomer mixture liquid. Into a reaction vessel, 18 parts by mass of methyl ethyl ketone, 0.03 parts by mass of 2-mercaptoethanol as a chain transfer agent, and 10% by mass (11.5 parts by mass) of the monomer mixture were placed and mixed, and the atmosphere was thoroughly replaced with nitrogen gas. On the other hand, the remaining 90% by mass (103.5 parts by mass) of the monomer mixture was mixed with 0.27 parts by mass of the chain transfer agent, 42 parts by mass of methyl ethyl ketone, and 3 parts by mass of the polymerization initiator 2,2'-azobis(2,4-dimethylvaleronitrile) "V-65" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and placed in a dropping funnel, and the mixed solution in the reaction vessel was heated to 75°C while stirring under a nitrogen atmosphere, and the mixed solution in the dropping funnel was dropped over 3 hours. After 2 hours at 75°C from the end of the dropping, a solution in which 3 parts by mass of the polymerization initiator was dissolved in 5 parts by mass of methyl ethyl ketone was added, and the mixture was further aged at 75°C for 2 hours and 80°C for 2 hours. Thereafter, methyl ethyl ketone was distilled off under reduced pressure drying to obtain an addition polymer E-1.

[0130] [Production of colorant particle dispersion] Production Example F1 (Production of Colorant Particle Dispersion F-1) In a 5L container equipped with a stirrer equipped with a dispersing blade, a reflux condenser, a dropping funnel, a thermometer and a nitrogen inlet tube, 75g of the addition polymer E-1 was dissolved in 620g of methyl ethyl ketone, and then 96g of a 5% by mass aqueous sodium hydroxide solution and 942g of deionized water were added as a neutralizing agent, and the mixture was stirred with a dispersing blade at 20°C for 10 minutes. Then, 300g of copper phthalocyanine pigment "ECB-301" (manufactured by Dainichi Seikagaku Kogyo Co., Ltd.) was added, and the mixture was stirred with a dispersing blade at 6400 rpm at 20°C for 2 hours. Then, the mixture was passed through a 200 mesh filter and treated with a homogenizer "Microfluidizer M-110EH" (manufactured by Microfluidics Co., Ltd.) at a pressure of 150 MPa for 15 passes. The resulting dispersion was stirred at 70°C under reduced pressure to remove methyl ethyl ketone and some of the water. The mixture was then passed through a 200 mesh filter, and deionized water was added to the mixture so that the solid content concentration was 20% by mass, thereby obtaining a colorant particle dispersion F-1. 50 The thickness was 0.12 μm and the CV value was 21%.

[0131] Manufacturing Example (Production of Toner 1) In a 3 L four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, 500 g of resin particle dispersion X-6, 35 g of release agent particle dispersion W-1, 35 g of release agent particle dispersion W-2, 63 g of colorant particle dispersion F-1, 10 g of a 10 mass% aqueous solution of polyoxyethylene (50) lauryl ether "EMULGEN 150" (manufactured by Kao Corporation, nonionic surfactant), and 10 g of a 15 mass% aqueous solution of sodium dodecylbenzenesulfonate "NEOPELEX G-15" (manufactured by Kao Corporation, anionic surfactant) were mixed at a temperature of 25° C. Next, while stirring the mixture, a solution in which 26 g of a 4.8 mass% aqueous solution of potassium hydroxide was added to an aqueous solution in which 35 g of ammonium sulfate was dissolved in 519 g of deionized water was dropped at 25° C. over 10 minutes, and the temperature was then raised to 65° C. over 2 hours, and the volume median particle diameter D of the aggregated particles was measured. 50 The temperature was maintained at 65° C. until the particle diameter reached 5.9 μm, to obtain an aggregated particle dispersion. Next, the dispersion of aggregated particles 1 was cooled to 59° C., and while maintaining the temperature at 59° C., 75 g of resin particle dispersion Y-1 was added over 90 minutes to obtain a dispersion of aggregated particles 2 in which the resin particles were aggregated into aggregated particles 1. To the obtained dispersion of aggregated particles 2, an aqueous solution of 41 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (Kao Corporation, anionic surfactant, effective concentration 27% by mass), 1396 g of deionized water, and 26 g of 0.1 mol / L aqueous sulfuric acid solution was added. The temperature was then raised to 75°C over 1 hour, and the mixture was kept at 75°C for 30 minutes. After that, 75 g of 0.1 mol / L aqueous sulfuric acid solution was added, and the mixture was further kept at 75°C for 15 minutes. Then, 25 g of 0.1 mol / L aqueous sulfuric acid solution was added again, and the mixture was kept at 75°C until the circularity reached 0.975, thereby obtaining a dispersion of fused particles in which aggregated particles were fused. The obtained dispersion of fused particles was cooled to 30°C, and the solid matter was separated by suction filtration, washed with deionized water at 25°C, and then vacuum dried at 30°C for 48 hours to obtain toner particles. The obtained toner particles had a volume median average particle size of 5.9 μm and a CV value of 21%. 100 parts by weight of the toner particles, 2.5 parts by weight of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 0.04 μm), and 1.0 part by weight of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Japan Co., Ltd., number average particle size: 0.012 μm) were placed in a Henschel mixer and stirred, and the mixture was passed through a 150 mesh sieve to obtain toner 1.

[0132] The minimum fixing temperature of the obtained toner 1 was measured by the following method and was found to be 110° C., demonstrating that toner 1 had excellent low-temperature fixing properties. [Low Temperature Fixability of Toner] Using a commercially available printer "Microline (registered trademark) 5400" (manufactured by Oki Data Corporation) on high-quality paper "J paper A4 size" (manufactured by Fuji Xerox Co., Ltd.), the amount of toner attached to the paper was 1.49 to 1.51 mg / cm 2A solid image of the above was printed on A4 paper with a length of 50 mm, leaving a margin of 5 mm from the top edge, without fixing. Next, the same printer was prepared with a temperature-variable fixing unit, the temperature of the fixing unit was set to 100°C, and the toner was fixed at a speed of 1.3 seconds per sheet in portrait orientation on A4 paper, to obtain a printout. In the same manner, the temperature of the fixing unit was increased by 5° C. each time, and the toner was fixed to obtain a printed matter. A piece of mending tape, Scotch (registered trademark) Mending Tape 810 (manufactured by Sumitomo 3M Limited, width 18 mm), was cut to a length of 50 mm and lightly applied to the top margin of the printed image over the solid image, and then a 500 g weight (contact area 1963 mm2) was applied. 2 ) was placed on the print and pressed against it once at a speed of 10 mm / s. The applied tape was then peeled off from the bottom end at a peeling angle of 180° and a speed of 10 mm / s to obtain a print after the tape had been peeled off. 30 sheets of high-quality paper "Excellent White Paper A4 Size" (manufactured by OKI Data Corporation) were placed under the print before and after the tape had been applied and peeled off, and the reflected image density of the fixed image portion of each print before and after the tape had been applied and peeled off was measured using a colorimeter "SpectroEye" (manufactured by GretagMacbeth, light irradiation conditions: standard light source D50, observation field of view 2°, density standard DINNB, absolute white standard), and the fixing rate was calculated from each reflected image density according to the following formula. Fixation rate (%) = (reflection image density after tape peeling / reflection image density before tape application) x 100 The lowest temperature at which the fixing rate was 90% or more was defined as the minimum fixing temperature. In this test, the lower the minimum fixing temperature, the better the low-temperature fixing property.

[0133] By using the aqueous dispersion of resin particles of the present invention, which has excellent emulsifiability and stability, toner can be produced stably.

Claims

1. the resin constituting the resin particles includes a composite resin in which a constituent part derived from a polyester resin and a constituent part derived from an addition polymerization resin are linked by a covalent bond; the constituent portion derived from the polyester resin is a polycondensate of an alcohol component and a carboxylic acid component, the carboxylic acid component contains a trivalent or higher polyvalent carboxylic acid, and the content of the trivalent or higher polyvalent carboxylic acid in the carboxylic acid component is 3 mol % or more and 20 mol % or less, The aqueous dispersion of resin particles contains the composite resin insoluble in methyl ethyl ketone in an amount of 5% by mass or more and 35% by mass or less.

2. An aqueous dispersion of resin particles as described in claim 1, wherein the alcohol component contains a propylene oxide adduct of bisphenol A, and the content of the propylene oxide adduct of bisphenol A in the alcohol component is 95 mol % or more.

3. An aqueous dispersion of resin particles as described in claim 1 or 2, wherein the amount of insoluble components in the composite resin in methyl ethyl ketone is more than 5 mass% and not more than 35 mass%.

4. 4. The aqueous dispersion of resin particles according to claim 1, wherein the content of the composite resin in the resin particles is 40% by mass or more and 100% by mass or less.

5. 5. The aqueous dispersion of resin particles according to claim 1, wherein the composite resin has an acid value of 10 mgKOH / g or more and 30 mgKOH / g or less.

6. 6. The aqueous dispersion of resin particles according to claim 1, wherein the composite resin is amorphous.

7. 7. The aqueous dispersion of resin particles according to claim 1, wherein the constituent portion derived from the addition polymerization resin is an addition polymer of a raw material monomer containing a styrene compound.

8. 8. The aqueous dispersion of resin particles according to claim 1, wherein the resin constituting the resin particles further contains a crystalline polyester resin.

9. A method for producing an aqueous dispersion of the resin particles according to any one of claims 1 to 8, comprising the steps of: The method for producing an aqueous dispersion of resin particles includes a step of dissolving the composite resin in an organic solvent, and then adding an aqueous medium to the organic solvent solution of the composite resin to effect phase inversion emulsification.

Citation Information

Patent Citations

  • Electrophotographic toner

    JP2007206540A

  • Dispersion liquid, method for preparing the same, and method for producing resin particle and toner

    JP2015091575A

  • Binder resin composition for electrophotographic toner

    JP2016099518A

  • Binder resin composition for toner

    JP2016130797A

  • Method for manufacturing aqueous dispersion of binder resin composition particle for electrophotographic toner

    JP2016133769A